2017
DOI: 10.1063/1.4976030
|View full text |Cite
|
Sign up to set email alerts
|

Lower bound of assortativity coefficient in scale-free networks

Abstract: The degree-degree correlation is important in understanding the structural organization of a network and the dynamics upon a network. Such correlation is usually measured by the assortativity coefficient r, with natural bounds r ∈ [−1, 1]. For scale-free networks with power-law degree distribution p(k) ∼ k −γ , we analytically obtain the lower bound of assortativity coefficient in the limit of large network size, which is not -1 but dependent on the power-law exponent γ. This work challenges the validation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Under the assumption that the distribution of the degrees satisfies a power law with infinite second moment, these bounds vanish as the size of the graph increases. The results in [56] are extended in [97], where a asymptotic lower bound for Pearson's correlation coefficient is obtained for scale-free networks. In particular for 1 < γ ≤ 3, it is shown that the limit of this measure is zero.…”
Section: Influence On Network Properties and Processesmentioning
confidence: 99%
“…Under the assumption that the distribution of the degrees satisfies a power law with infinite second moment, these bounds vanish as the size of the graph increases. The results in [56] are extended in [97], where a asymptotic lower bound for Pearson's correlation coefficient is obtained for scale-free networks. In particular for 1 < γ ≤ 3, it is shown that the limit of this measure is zero.…”
Section: Influence On Network Properties and Processesmentioning
confidence: 99%
“…The AS-level Internet topology represents simple and undirected graph = ( , ), where and are the AS node and edge sets, respectively. Because the topology inherits the nontrivial property of complex networks, it is usually described using some statistical properties such as degree, distance, and clustering [30][31][32][33][34][35][36]. A commonly used degree property is degree distribution ( ), which is the probability that a randomly selected node has k degrees.…”
Section: A Global Statistical Propertiesmentioning
confidence: 99%
“…In addition, the assortativity coefficient [33] shows the statistic of the node interconnectivity, which is defined as…”
Section: A Global Statistical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [9] this algorithm is used to obtain scaling results for Pearson's correlation coefficient, as introduced in [12] on maximally (dis)assortative graphs where the degrees follow a scale-free distribution. The results from [9] are extended in [21], where a lower bound for Pearson's correlation coefficient is established in scale-free graphs.…”
Section: Introductionmentioning
confidence: 99%